Pragmatics of Chinese As a Second Language. - Li, Shuai (Multilingual Matters, 2023)
This collection of empirical studies examines multiple aspects involved in the acquisition, teaching and assessment of pragmatics in second language Chinese. The studies address themes such as the acquisition of key pragmatic features, methodological innovations in pragmatics assessment, individual difference factors and virtual learning contexts.
Keywords: Second language acquisition.; Langue seconde -- Acquisition.; pragmatics.; LANGUAGE ARTS & DISCIPLINES / Study & Teaching